High-diffusion-channel sintered neodymium-iron-boron magnet and preparation method thereof

By slowly dehydrogenating during sintering to form diffusion channels, the problem of cracking in NdFeB magnets during sintering was solved, improving the yield and diffusion efficiency of heavy rare earth elements, and enhancing high-temperature coercivity.

CN120854151APending Publication Date: 2025-10-28NINGBO MAGNETIC NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510990943.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In the current technology for preparing NdFeB magnets, the undehydrogenated products are prone to cracking during sintering, resulting in a low magnet yield. Furthermore, the diffusion depth and utilization rate of heavy rare earth elements are insufficient, affecting the high-temperature coercivity.

Method used

By employing a slow dehydrogenation method, argon gas is introduced during the sintering process to control the heating rate and vacuum level, thereby forming diffusion channels, preventing magnet cracking, and improving the diffusion efficiency of heavy rare earth elements.

Benefits of technology

It improves the yield of magnets and the utilization rate of heavy rare earth elements, enhances the high-temperature coercivity of magnets, optimizes the diffusion effect of heavy rare earth elements, and prevents magnet cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005505826780000081
    Figure BDA0005505826780000081
Patent Text Reader

Abstract

According to the high-diffusion-channel sintered neodymium-iron-boron magnet and the preparation method thereof, a raw material casting piece is subjected to hydrogen decrepitation without dehydrogenation treatment, and then the raw material casting piece is formed into a product; sintering and tempering the product in sequence; the sintering conditions are as follows: vacuumizing to below 5 * 10 <-2 > Pa, heating at the speed of 5 DEG C / min, heating to 280 DEG C, keeping the temperature for 1-5 hours, reducing the vacuum degree to below 1 * 10 <-2 > Pa, filling argon into the furnace, and controlling the vacuum degree to be 10-400 Pa; the tempering conditions are as follows: argon is filled for cooling to 100 DEG C or below, the temperature is increased to 750-950 DEG C, heat preservation is performed for 1-4 hours, primary tempering is performed, argon is filled for cooling to 80 DEG C or below after heat preservation is finished, the temperature is increased to 440-700 DEG C, heat preservation is performed for 3-6 hours, secondary tempering is performed, argon is filled for cooling to 60 DEG C or below after heat preservation is finished, and the product is discharged from the furnace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to magnets and their preparation methods, and more specifically, to a high-diffusion-channel sintered NdFeB magnet and its preparation method. Background Technology

[0002] Neodymium iron boron (NdFeB) is currently the strongest rare-earth permanent magnet material, possessing a high magnetic energy product (8 MGOe ~ 64 MGOe), good coercivity (Hcj), and high temperature resistance. Its products are widely used in electric vehicles, wind power generation, variable frequency air conditioners, nuclear magnetic resonance imaging (NMR), optical disc drives, instruments, mineral processing, toys, and other fields.

[0003] In recent years, the rapid development of industries such as electric vehicles and wind power has continuously increased the demand for neodymium iron boron (NdFeB) magnets to meet the requirements of high-temperature applications. However, the coercivity of NdFeB magnets decreases with increasing temperature, and this decrease in coercivity at high temperatures increases the risk of magnet demagnetization. To improve the high-temperature coercivity of NdFeB magnets, it is generally achieved by partially replacing the light rare earth element Nd with the heavy rare earth element Dy or Tb. Due to the scarcity of heavy rare earth resources, the intensive utilization of heavy rare earth elements is a problem that needs to be solved from a cost perspective.

[0004] Currently, grain boundary diffusion of heavy rare earth elements (NREEs) has been widely studied as a method for the intensive utilization of NREEs. Through grain boundary diffusion, NREEs can be concentrated near the grain boundaries of sintered NdFeB magnets. While requiring a small amount of NREEs, it significantly improves coercivity and avoids a substantial decrease in remanence. Therefore, compared to the traditional method of adding NREEs during smelting, grain boundary diffusion is more advantageous for obtaining sintered NdFeB magnets with high overall performance.

[0005] Existing technologies already include deep grain boundary diffusion methods for obtaining NdFeB magnets. These methods utilize hydrogen atoms to enter the grain boundary phase and form efficient diffusion channels. After subsequent diffusion heat treatment, heavy rare earth elements enter the magnet through the diffusion channels, repairing defects on the grain surface and effectively increasing the diffusion depth of heavy rare earth elements. However, because hydrogen is released after the magnet is formed, magnet cracking is prone to occur, resulting in a low magnet yield. Summary of the Invention

[0006] The primary objective of this invention is to provide a method for preparing sintered NdFeB magnets with high diffusion channels, which slowly dehydrogenates the undehydrogenated product during sintering, thereby improving the magnet yield.

[0007] The first technical objective of this invention is achieved through the following technical solution:

[0008] A method for preparing a high-diffusion-channel sintered NdFeB magnet includes: hydrogenating a raw material casting sheet without dehydrogenation, and then molding it into a product; subjecting the product to sintering and tempering treatments sequentially; the sintering conditions are: vacuuming to 5x10⁻⁶ m³ / s. -2 Once the pressure drops below Pa, begin heating at a rate of 5°C / min, raising the temperature to 280°C and holding for 1–5 hours to reduce the vacuum level to 1 x 10⁻⁶. -2 Below Pa, argon gas is then introduced into the furnace, and the vacuum degree is controlled at 10-400 Pa. The temperature is then slowly increased to 920°C at a rate of 1°C / min. After reaching 920°C, the temperature is held for 0-5 hours until the vacuum degree drops to 1x10 Pa. -2 The product is heated to below Pa, then sintered at 1000-1100℃ for 2-10 hours. The tempering conditions are as follows: argon gas is introduced and cooled to below 100℃, then the temperature is raised to 750-950℃ and held for 1-4 hours for primary tempering. After holding, argon gas is introduced and cooled to below 80℃, then the temperature is raised to 440-700℃ and held for 3-6 hours for secondary tempering. After holding, argon gas is introduced and cooled to below 60℃ before the product is removed from the furnace.

[0009] Preferably, the raw material is processed into powder after hydrogen crushing. The powdering process includes adding 0.05-0.2% antioxidant to the coarse powder, grinding it in an air jet mill to a volume average particle size (SMD) of 2.5-5.0 micrometers, and adding 0.05-0.2% lubricant to the fine powder.

[0010] Preferably, the raw material after powdering is shaped and processed. The shaping process includes ensuring that the oxygen content in the sealed box is less than 0.05% under nitrogen protection, and shaping the powder in a mold with a magnetic field greater than 1.5T in the press to obtain a green body with a shaping density of 3.6 to 4.2 g / cm3. The green body has a size of 60.3 x 30.3 x 8.3 mm, with the 8.3 mm direction being the orientation direction.

[0011] Preferably, the isostatic pressing process after molding involves placing the blank wrapped in plastic film and vacuum-sealed into an isostatic press. Under a hydraulic pressure of 150–300 MPa, the density of the blank is further increased to 4.4–4.8 g / cm³.

[0012] Preferably, the raw materials are weighed according to the specified proportions, and the formula is: PrNd: 30.5wt%, B: 0.94wt%, Cu: 0.20wt%, Co: 0.20wt%, Ga: 0.10wt%, Zr: 0.15wt%, Fe balance.

[0013] Preferably, after surface treatment of the product after it leaves the furnace, the heavy rare earth elements are subjected to grain boundary diffusion treatment.

[0014] Preferably, the sintered product is machined to 60x30x8 and subjected to pickling or sandblasting surface pretreatment. Then, a 0.5% dysprosium film is deposited on the product by magnetron sputtering, followed by grain boundary diffusion treatment to obtain the final magnet.

[0015] The second objective of this invention is to provide a high-diffusion-channel sintered NdFeB magnet that slowly dehydrogenates undehydrogenated products during sintering, thereby improving the magnet yield.

[0016] A high-diffusion-channel sintered NdFeB magnet is obtained by a method for preparing a high-diffusion-channel sintered NdFeB magnet.

[0017] In summary, the present invention has at least one of the following beneficial effects:

[0018] (1) Compared with the traditional one-step diffusion technology, the advantage of this invention is that it does not dehydrogenate through the hydrogen crushing process, so that the magnet slowly dehydrogenates during heating, forming a channel that is conducive to subsequent grain boundary diffusion without cracking. In order to achieve the purpose of slow dehydrogenation, this invention adopts an argon-filled pressurized dehydrogenation method, which avoids cracking of the magnet due to excessively rapid dehydrogenation, and the slow dehydrogenation under pressure leaves hydrogen partially remaining in the grain boundary phase. This allows the hydrogen remaining in the magnet to be released during the diffusion heating process, creating vacancies or voids, thereby constructing a diffusion channel that is conducive to diffusion. The formation of this channel improves the diffusion efficiency of heavy rare earth elements, optimizes the diffusion effect of heavy rare earth elements, improves the utilization rate of heavy rare earth elements, and maximizes the grain boundary diffusion depth, thereby significantly improving the coercivity of the magnet.

[0019] (2) In traditional processes, if hydrogen is not dehydrogenated after hydrogen crushing, hydrogen will be released rapidly from the formed green blank during the sintering heating process. During this process, the green blank will be subjected to stress and generate large cracks, eventually leading to the cracking of the blank. In the sintering heating process of this invention, on the one hand, the heating rate is controlled by slowly raising the temperature so that the hydrogen release takes more time. On the other hand, argon is introduced to suppress the hydrogen release rate. Moreover, the product shrinks slowly during the heating process and the neodymium-rich phase gradually infiltrates and fills the micro-cracks, ultimately achieving the purpose of preventing the magnet from cracking. Detailed Implementation

[0020] Example 1: A method for preparing a high-diffusion-channel sintered NdFeB magnet, comprising the following steps:

[0021] Step 1, Ingredients: Weigh the raw materials according to the specified proportions. The formula is: PrNd: 30.5wt%, B: 0.94wt%, Cu: 0.20wt%, Co: 0.20wt%, Ga: 0.10wt%, Zr: 0.15wt%, Fe balance;

[0022] Step 2, Smelting: Raw materials are loaded into the quick-setting furnace crucible in the following order: iron bars, ferroborone and other fine scraps, praseodymium and neodymium. The quick-setting furnace is evacuated to below 5 Pa, and the material is dried. The drying power is set to 80KW~120KW. The material is dried for about 10~30 minutes. When the vacuum degree is below 3 Pa, argon gas is introduced to ~0.065Mpa. Then the power is increased to 500KW, and smelting begins. After the iron bars are melted, smelting continues for 8~10 minutes. The smelting power is adjusted to 360KW to refine the molten steel. The refining time is about 2~5 minutes. Once the alloy liquid surface turns silvery white, temperature measurement begins. When the temperature reaches the specified casting temperature ±10℃, casting begins to obtain the casting sheet.

[0023] Step 3, hydrogen crushing: The casting is placed in a hydrogen crushing furnace to absorb hydrogen until saturated, and then removed from the furnace without dehydrogenation treatment;

[0024] Step 4, Powdering: Add 0.05–0.2% antioxidant to the coarse powder and grind it in an air jet mill to achieve a volume average particle size (SMD) of 2.5–5.0 micrometers. The testing instrument is a Neopatek laser particle size analyzer. Add 0.05–0.2% lubricant to the fine powder.

[0025] Step 5, Molding: Under nitrogen protection, ensuring the oxygen content in the sealed chamber is less than 0.05%, the powder is molded in a mold with a magnetic field greater than 1.5T in the press to obtain a green compact with a molding density of 3.6-4.2 g / cm3 and a green compact size of 60.3 x 30.3 x 8.3 mm. 3 8.3 is the orientation direction;

[0026] Step 6, isostatic pressing: The blank wrapped in plastic film and vacuum sealed is placed in an isostatic press. Under a hydraulic pressure of 150-300 MPa, the density of the blank is further increased to 4.4-4.8 g / cm3.

[0027] Step 7, Sintering and Tempering: Under nitrogen protection, remove the vacuum bag and film, place the graphite box inside, quickly move it into the furnace, and evacuate to 5.0 x 10⁻⁶. -2 After the temperature drops below Pa, the temperature is increased at a rate of 5°C / min until it reaches 280°C. The temperature is then held for 1 to 5 hours. The purpose of this process is to remove the residual antioxidants and lubricants from the magnet. The upper limit of the temperature is set at 280°C because hydrogen will begin to be released from the magnet at 300°C. Therefore, this process is to remove the residual antioxidants and lubricants first.

[0028] Then reduce the vacuum level to 10. -2Below Pa; then argon gas is introduced into the furnace, the vacuum degree is controlled at 400Pa, and then the temperature is slowly increased to 920℃ at a heating rate of 1℃ / minute. This process achieves slow dehydrogenation of the product under pressure and slow heating by introducing argon gas and slow heating. The upper limit of the temperature is set at 920℃ because the product can basically dehydrogenate at around 900℃, but it will still be affected.

[0029] After reaching 920℃, maintain the temperature for 0–5 hours until the vacuum level drops to 10. -2 The temperature is below Pa, then raised to 1000-1100℃ for sintering for 2-10 hours; after sintering, argon gas is applied and cooled to below 100℃, then the temperature is raised to 750-950℃ and held for 1-4 hours for primary tempering, after which argon gas is applied and cooled to below 80℃, then the temperature is raised to 440-700℃ and held for 3-6 hours for secondary tempering, after which argon gas is applied and cooled to below 60℃ before being removed from the furnace;

[0030] To achieve slow dehydrogenation, this solution employs a method of gradual heating and increasing argon gas concentration. The principle is that the faster the heating rate, the faster the dehydrogenation. However, excessively rapid dehydrogenation can lead to product cracking. Therefore, by controlling the hydrogen release rate through slow heating, we can avoid irreparable cracking of the magnet. Argon gas pressurization for dehydrogenation further slows down the release of hydrogen from the magnet. Under normal circumstances, if the vacuum level is high, hydrogen in the magnet will escape more easily. If there is positive pressure, hydrogen will not escape from the magnet. At temperatures above 600 degrees Celsius, hydrogen may even undergo a disproportionation reaction with the magnet.

[0031] Step 8: Use a permanent magnet characteristic measuring instrument to measure the magnetic properties of the magnet, and use an H5500 hydrogen analyzer to test the hydrogen content of the magnet.

[0032] Step 9: Machin the sintered product to 60x30x8mm. 3 After surface pretreatment by pickling or sandblasting, the product is coated with 0.5% dysprosium film by magnetron sputtering. Then, the product is placed in a sintering furnace for high-temperature diffusion treatment to obtain the final magnet.

[0033] Example 2, a method for preparing a high diffusion channel sintered NdFeB magnet, differs from Example 1 in that, in step 7, argon gas is introduced into the furnace, the vacuum degree is controlled at 10 Pa, and then the temperature is slowly increased to 920°C at a heating rate of 1°C / min.

[0034] Example 3, a method for preparing a high diffusion channel sintered NdFeB magnet, differs from Example 1 in that, in step 7, argon gas is introduced into the furnace, the vacuum degree is controlled at 200 Pa, and then the temperature is slowly increased to 920°C at a heating rate of 1°C / minute.

[0035] Comparative Example 1, a method for preparing a high diffusion channel sintered NdFeB magnet, differs from Example 1 in that, in step 7, argon gas is then introduced into the furnace, the vacuum degree is controlled at 1 Pa, and then the temperature is slowly increased to 920°C at a heating rate of 1°C / min.

[0036] Comparative Example 2, a method for preparing a high-diffusion-channel sintered NdFeB magnet, differs from Example 1 in that, in step 7, sintering and tempering: under nitrogen protection, the vacuum bag and film are removed, the magnet is placed in a graphite box, rapidly fed into the furnace, and evacuated to a vacuum of 5.0 x 10⁻⁶. -2 After the pressure drops below Pa, begin heating. When the temperature reaches 800–900℃, hold for 3–6 hours to reduce the vacuum to 10. -2 The temperature is below Pa, then raised to 1000-1100℃ for sintering for 2-10 hours; after sintering, argon gas is applied and cooled to below 100℃, then the temperature is raised to 750-950℃ and held for 1-4 hours for primary tempering, after which argon gas is applied and cooled to below 80℃, then the temperature is raised to 440-700℃ and held for 3-6 hours for secondary tempering, after which argon gas is applied and cooled to below 60℃ before being removed from the furnace.

[0037] Comparative Example 3, a method for preparing a high-diffusion-channel sintered NdFeB magnet, comprising the following steps:

[0038] Step 1, Ingredients: Weigh the raw materials according to the specified proportions. The formula is: PrNd: 30.5wt%, B: 0.94wt%, Cu: 0.20wt%, Co: 0.20wt%, Ga: 0.10wt%, Zr: 0.15wt%, Fe balance.

[0039] Step 2, Smelting: Raw materials, such as iron bars, ferroboron, and praseodymium-neodymium, are sequentially loaded into the crucible of the quick-setting furnace. The quick-setting furnace is evacuated to below 5 Pa, and the material is dried. The drying power is set to 80KW~120KW. The material is dried for about 10~30 minutes. When the vacuum degree is below 3 Pa, argon gas is introduced to ~0.065Mpa. Then the power is increased to 500KW, and smelting begins. After the iron bars are melted, smelting continues for 8~10 minutes. The smelting power is adjusted to 360KW, and the molten steel is refined and smelted. The refining and smelting time is about 2~5 minutes. Once the surface of the alloy liquid turns silvery white, temperature measurement begins. When the temperature reaches the specified casting temperature ±10℃, casting begins, and a casting sheet is obtained. Step 3, Hydrogen Dehydrogenation: The casting sheet is placed in a hydrogen dehydrogenation furnace to absorb hydrogen until saturated. Then it is heated to 600℃ for primary dehydrogenation to below 20 Pa. Step 4, Powdering: Add 0.05–0.2% antioxidant to the coarse powder and grind it in an air jet mill to achieve a volume average particle size (SMD) of 2.5–5.0 micrometers. The testing instrument is a Neopatek laser particle size analyzer. Add 0.05–0.2% lubricant to the fine powder.

[0040] Step 5, Molding: Under nitrogen protection, ensure that the oxygen content in the sealed box is less than 0.05%. The powder is molded in a mold with a magnetic field greater than 1.5T to obtain a green body with a molding density of 3.6 to 4.2 g / cm3. The green body size is 60.5 x 30.5 x 43.5, with the 43.5 direction being the orientation direction.

[0041] Step 6, isostatic pressing: The blank wrapped in plastic film and vacuum sealed is placed in an isostatic press. Under oil pressure of 150-300 MPa, the density of the blank is further increased to 4.4-4.8 g / cm3.

[0042] Step 7, Sintering and Tempering: Under nitrogen protection, remove the vacuum bag and film, place the graphite box inside, quickly move it into the furnace, and evacuate to 5.0 x 10⁻⁶. -2 After the pressure drops below Pa, begin heating. When the temperature reaches 800–900℃, hold for 3–6 hours to reduce the vacuum to 10. - 2 The temperature is below Pa, then raised to 1000-1100℃ for sintering for 2-10 hours; after sintering, argon gas is applied and cooled to below 100℃, then the temperature is raised to 750-950℃ and held for 1-4 hours for primary tempering, after which argon gas is applied and cooled to below 80℃, then the temperature is raised to 440-700℃ and held for 3-6 hours for secondary tempering, after which argon gas is applied and cooled to below 60℃ before being removed from the furnace.

[0043] Step 8: Use a permanent magnet characteristic measuring instrument to measure the magnetic properties of the magnet, and use an H5500 hydrogen analyzer to test the hydrogen content of the magnet.

[0044] Step 9: The sintered product is machined to 60x30x8 and then subjected to pickling or sandblasting surface pretreatment. Then, a 0.5% dysprosium film is deposited on the product by magnetron sputtering. Finally, grain boundary diffusion treatment is performed to obtain the final magnet.

[0045] The initial and diffused sintered NdFeB magnets prepared above in the examples and comparative examples were measured using a permanent magnet property measuring instrument, and their properties are shown in Table 1 below:

[0046] Table 1

[0047]

[0048] As can be seen from Table 1:

[0049] In Comparative Example 1, because the vacuum level was too low after argon was introduced (1 Pa), hydrogen was released more easily. Although the initial magnet and the diffused magnet had higher magnetic properties than those prepared in Comparative Example 3, the rapid release caused 12% of the initial magnet to crack, and the problem of magnet cracking was not completely solved.

[0050] In Comparative Example 2, the initial magnets prepared by the method all cracked due to the use of a rapid heating sintering process. This is because in the traditional process, if hydrogen is not dehydrogenated after hydrogen fragmentation, hydrogen will be rapidly released from the formed green blank during the sintering heating process. During this process, the green blank will be subjected to stress, resulting in large cracks, which will eventually lead to the cracking of the blank. In the heating process of the present invention, on the one hand, the heating rate is controlled so that the hydrogen release takes more time, and on the other hand, argon gas is introduced to suppress the hydrogen release rate. Moreover, the product shrinks slowly during the heating process and the neodymium-rich phase gradually infiltrates and fills the micro-cracks, ultimately achieving the purpose of preventing the magnet from cracking.

[0051] Comparative Example 3 is a conventional process involving hydrogen crushing, dehydrogenation, and sintering.

[0052] Obviously, the initial magnets and diffused magnets prepared by the methods described in Example 1 (argon vacuum of 400 Pa), Example 2 (argon vacuum of 10 Pa), and Example 3 (argon vacuum of 200 Pa) have higher remanence, coercivity, and energy product, and higher Hk / Hcj (squareness Q) compared to Comparative Examples 1 to 3.

[0053] Example 4: A high-diffusion-channel sintered NdFeB magnet prepared using any one of the methods in Examples 1-3.

[0054] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a high-diffusion-channel sintered NdFeB magnet, characterized in that: include: The raw material castings are hydrogen-crushed without dehydrogenation treatment, and then molded into products; The product undergoes sintering and tempering treatments sequentially. The sintering conditions are: vacuuming to 5x10 -2 Once the pressure drops below Pa, begin heating at a rate of 5°C / min, raising the temperature to 280°C and holding for 1–5 hours to reduce the vacuum level to 1 x 10⁻⁶. -2 Below Pa, argon gas is then introduced into the furnace, and the vacuum degree is controlled at 10-400 Pa. The temperature is then slowly increased to 920°C at a rate of 1°C / min. After reaching 920°C, the temperature is held for 0-5 hours until the vacuum degree drops to 1x10 Pa. -2 Below Pa, then heat to 1000-1100℃ for sintering for 2-10 hours; The tempering conditions are as follows: purge with argon gas and cool to below 100°C, raise the temperature to 750-950°C and hold for 1-4 hours for primary tempering, after which purge with argon gas and cool to below 80°C, raise the temperature to 440-700°C and hold for 3-6 hours for secondary tempering, after which purge with argon gas and cool to below 60°C to remove the product from the furnace.

2. The method for preparing a high-diffusion-channel sintered NdFeB magnet according to claim 1, characterized in that: The raw material is processed into powder after hydrogen crushing. The powdering process includes adding 0.05-0.2% antioxidant to the coarse powder, grinding it in an air jet mill to a volume average particle size (SMD) of 2.5-5.0 micrometers, and adding 0.05-0.2% lubricant to the fine powder.

3. The method for preparing a high-diffusion-channel sintered NdFeB magnet according to claim 2, characterized in that: The raw material after powdering is shaped and processed. The shaping process includes ensuring that the oxygen content in the sealed box is less than 0.05% under nitrogen protection. The powder is shaped in a mold with a magnetic field greater than 1.5T in the press to obtain a green body with a shaped density of 3.6 to 4.2 g / cm3. The green body size is 60.3 x 30.3 x 8.3 mm, and the 8.3 mm direction is the orientation direction.

4. The method for preparing a high-diffusion-channel sintered NdFeB magnet according to claim 3, characterized in that: The isostatic pressing process after molding involves placing the blank, which is wrapped in plastic film and vacuum-sealed, into an isostatic press. Under hydraulic pressure of 150–300 MPa, the density of the blank is further increased to 4.4–4.8 g / cm³.

5. The method for preparing a high-diffusion-channel sintered NdFeB magnet according to claim 1, characterized in that: The raw materials were weighed according to the specified proportions, and the formula was as follows: PrNd: 30.5wt%, B: 0.94wt%, Cu: 0.20wt%, Co: 0.20wt%, Ga: 0.10wt%, Zr: 0.15wt%, Fe balance.

6. The method for preparing a high-diffusion-channel sintered NdFeB magnet according to claim 1, characterized in that: After surface treatment, the heavy rare earth elements are subjected to grain boundary diffusion treatment.

7. The method for preparing a high-diffusion-channel sintered NdFeB magnet according to claim 6, characterized in that: The sintered product is machined to 60x30x8 and then subjected to pickling or sandblasting surface pretreatment. Next, a 0.5% dysprosium film is deposited on the product by magnetron sputtering, followed by grain boundary diffusion treatment to obtain the final magnet.

8. A high-diffusion-channel sintered NdFeB magnet prepared by the method according to any one of claims 1 to 7.